Qualidade da orientação nutricional intra-hospitalar em pacientes com infarto agudo do miocardio da rede pública e privada de saúde em Sergipe: registro VICTIM - Lima, Ticiane Clair Remacre Munareto (2018)
BACKGROUND: The change in eating habits is part of the set recommendations after STEMI (ST-Elevation Myocardial Infarction). Studies demonstrated disparities in the quality of care between public and private health services, but the quality of care offered for nutritional counseling is little explored. OBJECTIVE: Evaluate the quality of intra-Hospital nutrition orientation among patients with STEMI of the public and private health system in Sergipe. METHODS: A cross-sectional, quantitative study, that used data from the VICTIM Registry, with patients ≥ 18 years, diagnosed with STEMI, from April to November 2017, in 1 hospital with SUS care and 3 private ones. The occurrence of nutritional orientation and its quality were analyzed. RESULTS: 188 patients were analyzed, of which 80.3% were from the public health service. Among the interviewees, 57,6% of the public health service and 70.3% of the private (p = 0,191) received intra-Hospital nutrition orientation. The record, in medical records, of this practice was lower in the public service (2,6% vs. 37,8%, p<0,001). Both services had a prevalence of less than 50% orientation in most of the evaluated items. There was a predominance of restrictive guidelines, mainly salt and fat, respectively of 50,3% and 70,3% (p = 0,064), in the public and private sectors. As for the insertion of cardioprotective foods, patients from the private network were more benefited, mainly in fruit, vegetable / vegetable consumption (48.6% vs. 13.2%, p <0.001). Among those who received guidance, nutritional knowledge was higher in the private sector (68.2% vs. 26.3%, p <0.001). CONCLUSIONS: The intra-Hospital nutritional orientation given to patients with IAMCSST in Sergipe still has poor quality in both services, especially in the health public.